A STUDY ON THE PLIGHT OF WOMEN WORKERS IN THE INFORMAL - CHANDRIKA RAM (International Journal of Multidisciplinary Research and Studies, 2020)
The fact that women are disproportionately represented in the lowest-paying, most precarious jobs in the informal economy is a clear indication that their labour is invisible. The informal sector, also known as the grey economy or the hidden economy, is responsible for the provision of employment and income without being subject to the regulation or control of the government or a social safety net (e.g., pension, fair wages, or unemployment insurance). Domestic workers are employed in private houses to perform a variety of activities. These services include sweeping and cleaning, washing clothing and dishes, grocery shopping and cooking, as well as providing care for children, the elderly, and the handicapped. Additionally, they provide services in the areas of gardening, driving, and security. Some people do this sort of employment while also living on the grounds of their employer.